Poeta przed kompasem - Zieliński, Jan (Załącznik Kulturoznawczy, 2022)
The paper discusses the importance of the motif of clocks and sundials in the biography of the Eighteens century poet Franiszek Dionizy Kniaźnin and shows various stages of an image – in subsequent Polish poetry and prose – of this poet, deranged in his late years, after the fall of the independent Poland, as he used to stand for hours in front of a sundial, staring at the movement of the shadow and contemplating the arrival of his own end as well. This presentation covers a period of more than 170 years.